Aid, infrastructure and growth - Mti, Sehlule Nontutuzelo (School of Economics, 2015)
In their seminal paper, Burnside and Dollar (2000) introduced the interactive term aid*policy into growth equations. Most studies up until then had merely added aid as a variable on its own with GDP growth as the dependent variable in order to check aid effectiveness.